MEASLES ВОЗМОЖНОСТИ TREATMENT OPTIONS AT THE PRESENT STAGE - Abdulloev Mukhriddin Ziedulloevich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
A  clinical  follow-up  and  treatment  of  72  children  aged  from  5  months  was performed. Up to 3 years of age with measles. 68 people (94.4%) were diagnosed with a typical moderate form, 4 people (5.6%) with an atypical (mitigated) mild form of the disease. All the children were not vaccinated against measles. A typical moderate form of measles was characterized by a cyclical course with a change in classical periods and the presence of characteristic clinical syndromes. Pathognomonic symptoms were revealed: Belsky-Filatov-Koplik spots (67.7%), stage rash (100%), stage pigmentation (100%). Etiotropic therapy was performed with VIFERON. The rapid disappearance of intoxication and normalization of body temperature, an early decrease in the severity and  duration  of  catarrhal  syndrome,  a  decrease  in  the  severity  and  frequency  of complications, and the absence of ARVI stratification were revealed.